Manifestasi Klinis COVID-19 dalam Bidang Dermatologi - Keneyzia Gliselda (Jurnal Medika Hutama, 2022)
Coronavirus 2019 (COVID-19) is a disease that was first discovered at the end of 2019, which was later declared a world pandemic by the World Health Organization (WHO) in early 2020. COVID-19 is caused by a new virus called Severe Acute Respiratory Syndrome Coronavirus. 2 (SARS-CoV-2). Clinical symptoms of COVID-19 in general are fever, cough, fatigue, sputum production, headache, and quickly progress to respiratory failure, organ failure and even death. In addition, some patients have reported cutaneous manifestations. Knowledge of clinical manifestations in the field of dermatology is expected to assist clinicians in handling COVID-19 patients with skin manifestations.